(untitled) (PERcursos Linguísticos, 2020)
Considering the relevance of the articulation between the school, family and community spheres, this communication aims to discuss the impacts of a community literacy project (CLP) on the resizing of speech, reading and writing practices in the school space, based on statements produced by collaborators within the scope of the project under analysis. The theoretical contribution of this investigation comes from New Literacy Studies, especially literacy and CLP practices, from the Bakhtin Circle and New Rhetoric, with regard to considerations on genres. From the qualitative paradigm and the ethnographic-critical approach, data generation took place in a public school in Natal - RN - Brazil, promoting an extension action, materialized as a CLP, entitled “Nova(s) Descoberta(s) of our neighborhood”: school, family and community ”, with collaborating students from a class of first year of elementary school, members of the school team, family members of students and community agents from the neighborhood of Nova Descoberta, where the school is located, and its surroundings. The action resulted in an e-book, in which the collaborators’ local knowledge is presented from their productions, oral, written and multisemiotic, in genres such as reports, interviews, presentation, stories, comments and others. The analysis of these statements demonstrates, among different aspects, the social issues specific to the neighborhood, the interests and motivations of the research subjects, the implications of the CLP in learning, the distribution of tasks in collaborative works, the role of writing to promote access to new worlds and cultural experiences built from the speeches of collaborators, mobilized as tools for acting in social life.